The ultrastructure of hepatic endothelial cells in the correction of steatosis with new biologically active compound Angiolin - K. V. Pivtorak; I. A. Mazur; M. A. Voloshyn (Patologìâ)
Aim. To characterize the ultrastructural organization of endothelial cells, hepatocytes in correction of experimental hepatic steatosis with Angiolin.